High-emissivity energy-saving coating and preparation method thereof
By combining alkenyl silicon carbide with thiol POSS in high-emissivity coatings, polymerizing the surface of phenolic resin with silicon carbide, combining components such as nickel-doped lanthanum aluminate-based ceramic powder, high-emissivity energy-saving coatings are prepared, which solves the problems of insufficient adhesion of existing coatings and filler agglomeration, and achieves efficient thermal energy utilization and thermal shock resistance.
Patent Information
- Application Number
- CN202510091362.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
AI Technical Summary
The existing high-emissivity coatings have insufficient adhesion on the substrate, and the filler is prone to agglomeration, which has poor compatibility with organic film forming substances, affecting the performance of the coating.
By combining alkenyl silicon carbide with thiol POSS, and polymerizing the surface of the phenolic resin with silicon carbide to form a silicon carbide/phenolic resin composite material, combined with nickel-doped lanthanum aluminate-based ceramic powder and other components, a high emissivity and energy-saving coating was prepared.
After the coating is coated and cured on the substrate, the coating has good mechanical properties, good thermal shock resistance and high emissivity. It can effectively improve the thermal energy utilization rate of the substrate, extend the service life of the kiln, and reduce energy consumption.
Smart Images

Figure CN119842287A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a high-emissivity energy-saving coating and a preparation method thereof. Background Art
[0002] High emissivity coatings are developed from protective coatings. They have excellent radiation properties and can enhance the absorption and emission of heat in the form of infrared radiation, thereby increasing thermal radiation and strengthening heat dissipation. They have good heat transfer properties at high temperatures. High emissivity materials are widely used in the field of energy conservation and environmental protection, and are mainly used in industrial kilns and heat exchangers. When the operating temperature exceeds 1000°C, the heat inside industrial kilns and heat exchangers is transferred by radiation. After spraying high emissivity energy-saving materials on the surface of the lining of industrial kilns, the thermal radiation efficiency is improved, the temperature uniformity in the furnace is improved, and the heat loss is reduced, which can protect the lining of the kiln, extend the service life of the kiln, reduce energy consumption, and improve energy utilization efficiency.
[0003] Existing technologies such as Chinese patent CN105111935A disclose a high-temperature resistant and high-radiation thermal control coating and a preparation method thereof, in which rare earth oxides and silicon carbide are used as fillers, and polyborosilazane, polysiloxazane or high-temperature resistant silicone resin is used as a film-forming material. The two are mixed to form a thermal control coating, which has the advantages of high temperature resistance, high emissivity, and strong thermal shock resistance. However, since the filler is easy to agglomerate and has poor compatibility with the organic film-forming material, the adhesion of the coating on the substrate is affected. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-emissivity energy-saving coating and a preparation method thereof. After the coating is coated and cured on a substrate, it has excellent mechanical properties, good thermal shock resistance, and high emissivity, which can effectively improve the thermal energy utilization rate of the substrate and play a role in energy saving and consumption reduction.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a high-emissivity energy-saving coating comprises the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS and toluene, ultrasonically dispersing and reacting, and after the reaction is completed, filtering, washing and drying to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder is mixed with a hydrogen chloride aqueous solution, stirred, centrifuged, filtered, washed, and dried after the treatment to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, the pretreated silicon carbide powder, and ethanol are mixed and ball-milled, and dried to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: Mix (3-mercaptopropyl)trimethoxysilane and methanol, add aqueous hydrogen chloride solution, stir to react, and after the reaction is completed, stand to cool, filter, and purify to obtain mercapto POSS; Step (2), mixing mercapto silicon carbide, dibutylamine and acetone, ultrasonically dispersing, dropping 4-hydroxyphenyl acrylate-acetone mixed solution, reacting after the dropwise addition, and rotary evaporating after the reaction to obtain phenolic silicon carbide; Phenol, boric acid, a catalyst and toluene are mixed and reacted. After the reaction is completed, phenolic silicon carbide and paraformaldehyde are added and the reaction is continued. After the reaction is completed, the silicon carbide / phenolic resin composite material is obtained by rotary evaporation and drying. Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent to obtain a high-emissivity energy-saving coating.
[0006] Preferably, in step (1), the mass ratio of alkenyl silicon carbide, mercapto POSS and toluene is 8:40-50:200-250; and the reaction conditions are: reacting under ultraviolet light with a wavelength of 365 nm and a temperature of 20-30° C. for 12-16 hours.
[0007] Preferably, when preparing alkenyl silicon carbide in step (1): the mass ratio of silicon carbide powder to hydrogen chloride aqueous solution is 1:40-50, and the hydrogen chloride aqueous solution is 0.1 mol / L hydrogen chloride aqueous solution; the stirring treatment conditions are: stirring treatment at room temperature for 3-5 hours; the mass ratio of γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol is 0.1-0.12:100:80-100; and the ball milling time is 10-12 hours.
[0008] Preferably, when preparing mercapto POSS in step (1): the volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and aqueous hydrogen chloride solution is 14-16:350-400:35-37, and the aqueous hydrogen chloride solution is 37 wt % aqueous hydrogen chloride solution; the stirring reaction conditions are: stirring the reaction at a temperature of 90-100° C. for 30-36 hours.
[0009] Preferably, the purification operation comprises: taking the precipitate obtained after filtration, adding 5-8 times the mass of dichloromethane to dissolve the precipitate, then adding 8-10 times the mass of precipitate methanol at 0°C to precipitate, repeating the dissolution and precipitation operations to obtain a crude reaction product; mixing and dissolving the crude reaction product with dichloromethane at a mass ratio of 1:6-8, then adding 8-10 times the mass of the crude reaction product water to extract, separate the liquids, take the organic phase, add 15-20wt% of anhydrous magnesium sulfate by mass of the organic phase, stand and remove water for 0.5-1h, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation at a temperature of 20-30°C.
[0010] Preferably, in step (2), the mass ratio of mercapto silicon carbide, dibutylamine, acetone, and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.5-0.6:18-22:15-17; the 4-hydroxyphenyl acrylate-acetone mixed solution is prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:20-25, and the dropwise addition time is 40-60 min; when preparing phenolic silicon carbide, the reaction conditions are: stirring the reaction at room temperature for 4-6 h.
[0011] Preferably, in step (2), the mass ratio of phenol, boric acid, catalyst, toluene, phenolic silicon carbide and paraformaldehyde is 4.4-4.8:1.2-1.3:0.1-0.2:60-80:6:7.6-8; when preparing the silicon carbide / phenolic resin composite material, the reaction conditions are: reacting at a temperature of 115-125°C for 5-6h, and the continued reaction conditions are: continuing the reaction at a temperature of 100-110°C for 2.5-3h.
[0012] Furthermore, the catalyst includes oxalic acid.
[0013] Preferably, in step (3), the mass ratio of the silicon carbide / phenolic resin composite material, the nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent is 40:20-25:4-5:3-4:20-25:5-10:5-8:15-20.
[0014] Furthermore, the solvent includes xylene.
[0015] Preferably, the nickel-doped lanthanum aluminate-based ceramic powder in step (3) is prepared by the following steps: Lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate and nickel chloride hexahydrate are mixed in a molar ratio of 5:3:2 to obtain a precursor mixture, the precursor mixture, ethanol and citric acid are mixed and dissolved in a mass ratio of 2:1:1 to form a precursor solution, and the mixture is stirred and reacted at 80°C until the precursor solution is converted into a colloid. After the reaction is completed, the mixture is dried at 105°C for 48 hours, crushed, passed through a 400-mesh sieve, and calcined at 900°C for 4 hours to obtain nickel-doped lanthanum aluminum oxide-based ceramic powder.
[0016] Preferably, a high emissivity energy-saving coating is prepared using the method for preparing the high emissivity energy-saving coating as described above.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention uses a thiol-ene click chemical reaction to compound alkenyl silicon carbide surface-modified by a vinyl silane coupling agent with a thiol POSS prepared by a hydrolysis condensation reaction of (3-mercaptopropyl)trimethoxysilane to obtain a thiol silicon carbide having a large number of thiol groups and POSS structures on the surface, and grafts and compounds the thiol silicon carbide with 4-hydroxyphenyl acrylate by a Michael addition reaction to obtain a phenolic silicon carbide with a phenolic terminal group. The phenolic silicon carbide can be introduced into a synthesis process of a phenolic resin as a special phenol and used as a carrier to polymerize the phenolic resin on the surface of the silicon carbide. The present invention introduces boron into the phenolic resin structure by utilizing boric acid and phenol to undergo an esterification reaction, and then uses phenolic silicon carbide as a carrier to polymerize the boron-containing phenolic resin on the surface of the silicon carbide carrier to form a silicon carbide / phenolic resin composite material. This not only improves the compatibility of silicon carbide with organic components in the coating, but also, due to the introduction of the phenolic resin structure, has hydrogen bonding and other interaction forces with the organic silicon component polyborosilazane and the adhesive in the coating, thereby improving the bonding performance of the coating on the surface of the substrate. The present invention mixes silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and organic solvent uniformly, and the obtained high-emissivity energy-saving coating has good mechanical properties, good thermal shock resistance, and high emissivity after being coated and cured on a substrate, and can effectively improve the thermal energy utilization rate of the substrate, thereby playing a role in energy saving and consumption reduction; Among them, nickel-doped lanthanum aluminate-based ceramic powder and silicon carbide both have excellent emissivity, which can improve the infrared emissivity of the coating; the boron element and POSS structure in the silicon carbide / phenolic resin composite material can effectively improve the residual mass of the phenolic resin cracking product, increase the content of silicon and boron in the cracking product, and undergo a ceramic reaction under a high-temperature ablation environment to produce SiO2, SiC and other substances; the main components of polyborosilazane and adhesives are organic polyborosilazane, which is rich in silicon and boron elements and will undergo a ceramic reaction under a high-temperature ablation environment, transforming into a ceramic structure with high temperature resistance and high bonding strength; the synergistic effect between silicon carbide / phenolic resin composite materials, polyborosilazane and adhesives has significantly improved the heat resistance, high-temperature bonding performance, thermal shock resistance and high-temperature mechanical strength of the coating material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a process flow chart for preparing high-emissivity energy-saving coating in the present invention; Figure 2 is a schematic diagram of the reaction for preparing phenolic silicon carbide in the present invention; Figure 3 It is a histogram of the emissivity of samples 1-7 in the present invention. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] Example 1 This embodiment discloses a method for preparing a high-emissivity energy-saving coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS and toluene in a mass ratio of 8:40:200, ultrasonically dispersing for 20 minutes, reacting for 16 hours at 20°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 6 times the mass of the filter cake to wash three times, and drying at 80°C for 24 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:40, and stirred at room temperature for 3 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and washed with water 5 times the mass of the filter cake until it was neutral, and dried at 100°C for 6 hours to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed and ball-milled at a mass ratio of 0.1:100:80 for 10 hours, and dried at 100°C for 10 hours to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: Mix (3-mercaptopropyl)trimethoxysilane with methanol, add 37wt% hydrogen chloride aqueous solution, the volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% hydrogen chloride aqueous solution is 14:350:35, stir and react at 90°C for 36h, after the reaction is completed, let it stand and cool for 0.5h, filter and remove the supernatant, take the precipitate, add 5 times the mass of dichloromethane to dissolve the precipitate, then add 8 times the mass of precipitate to precipitate at 0°C, repeat the dissolution and precipitation operation once to obtain a crude reaction product; mix and dissolve the crude reaction product with dichloromethane in a mass ratio of 1:6, then add 8 times the mass of water to extract the crude reaction product, separate the liquids, take the organic phase, add 15wt% of anhydrous magnesium sulfate by mass of the organic phase, let it stand and remove water for 1h, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation at 20°C to obtain mercapto POSS; Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 10 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:25 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.5:18:15, and the dropping time is 40 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 4 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 20°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene are mixed and reacted at 115°C for 6 hours. After the reaction, phenolic silicon carbide and polyformaldehyde are added and the reaction is continued at 100°C for 3 hours. After the reaction is completed, the solvent toluene is removed by rotary evaporation at 120°C and dried at 70°C for 6 hours to obtain a silicon carbide / phenolic resin composite material. Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.4:1.2:0.1:60:6:7.6; Step (3), mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene in a mass ratio of 40:20:4:3:20:10:5:15 to obtain a high-emissivity energy-saving coating; The nickel-doped lanthanum aluminate-based ceramic powder is prepared by the following steps: Lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate and nickel chloride hexahydrate are mixed in a molar ratio of 5:3:2 to obtain a precursor mixture, the precursor mixture, ethanol and citric acid are mixed and dissolved in a mass ratio of 2:1:1 to form a precursor solution, and the mixture is stirred and reacted at 80°C until the precursor solution is converted into a colloid. After the reaction is completed, the mixture is dried at 105°C for 48 hours, crushed, passed through a 400-mesh sieve, and calcined at 900°C for 4 hours to obtain nickel-doped lanthanum aluminum oxide-based ceramic powder.
[0021] Example 2 This embodiment discloses a method for preparing a high-emissivity energy-saving coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS, and toluene in a mass ratio of 8:43:230, ultrasonically dispersing for 25 minutes, reacting for 14 hours at 25°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 6 times the mass of the filter cake to wash three times, and drying at 85°C for 22 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:45, and stirred at room temperature for 3 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and washed with water 5 times the mass of the filter cake until it was neutral, and dried at 110°C for 5 hours to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed at a mass ratio of 0.1:100:90, ball-milled for 11 hours, and dried at 110°C for 10 hours to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: (3-mercaptopropyl)trimethoxysilane is mixed with methanol, and a 37wt% aqueous solution of hydrogen chloride is added. The volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% aqueous solution of hydrogen chloride is 14.5:380:35.5. The mixture is stirred at 95°C for 33h. After the reaction is completed, the mixture is allowed to stand for cooling for 0.5h. The supernatant is filtered out to remove the precipitate. The precipitate is dissolved by adding 5 times the mass of dichloromethane, and then 8 times the mass of methanol at 0°C is added for precipitation. The dissolution and precipitation operations are repeated once to obtain a crude reaction product. The crude reaction product is mixed and dissolved with dichloromethane at a mass ratio of 1:7, and then 8 times the mass of water is added to extract the crude reaction product. The organic phase is separated, and anhydrous magnesium sulfate of 15wt% of the mass of the organic phase is added to stand for dehydration for 0.8h. The mixture is filtered and the filtrate is evaporated to remove the solvent dichloromethane at 25°C to obtain mercapto POSS. Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 15 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:22 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.5:20:15.5, and the dropping time is 50 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 5 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 25°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene were mixed and reacted at 120°C for 5 hours. After the reaction, phenolic silicon carbide and paraformaldehyde were added and the reaction was continued at 105°C for 2.5 hours. After the reaction was completed, the solvent toluene was removed by rotary evaporation at 125°C and dried at 75°C for 5 hours to obtain a silicon carbide / phenolic resin composite material. Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.5:1.23:0.15:70:6:7.7; Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene in a mass ratio of 40:22:4.3:3.3:22:8:6:18 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0022] Example 3 This embodiment discloses a method for preparing a high-emissivity energy-saving coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS, and toluene in a mass ratio of 8:45:230, ultrasonically dispersing for 25 minutes, reacting for 14 hours at 25°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 7 times the mass of the filter cake to wash three times, and drying at 85°C for 22 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:45, and stirred at room temperature for 4 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and water 6 times the mass of the filter cake was added to wash the filter cake until it was neutral, and dried at 110°C for 5 hours to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed at a mass ratio of 0.11:100:90, ball-milled for 11 hours, and dried at 110°C for 9 hours to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: (3-mercaptopropyl)trimethoxysilane is mixed with methanol, and a 37wt% aqueous solution of hydrogen chloride is added. The volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% aqueous solution of hydrogen chloride is 15:380:36. The mixture is stirred at 95°C for 33h. After the reaction is completed, the mixture is allowed to stand for cooling for 0.8h. The supernatant is filtered to remove the precipitate. The precipitate is dissolved by adding dichloromethane 6 times the mass of the precipitate, and then 8 times the mass of the precipitate is added for precipitation at 0°C. The dissolution and precipitation operations are repeated once to obtain a crude reaction product. The crude reaction product is mixed and dissolved with dichloromethane at a mass ratio of 1:7, and then 8 times the mass of the crude reaction product is added for extraction. The mixture is separated, the organic phase is taken, anhydrous magnesium sulfate 18wt% of the mass of the organic phase is added, and the mixture is allowed to stand for dehydration for 0.8h. The mixture is filtered, and the solvent dichloromethane is removed by rotary evaporation at 25°C to obtain mercapto POSS. Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 15 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:22 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.55:20:16, and the dropping time is 50 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 5 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 25°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene were mixed, reacted at 120°C for 5.5 hours, phenolic silicon carbide and paraformaldehyde were added after the reaction, and the reaction was continued at 105°C for 2.5 hours. After the reaction was completed, the solvent toluene was removed by rotary evaporation at 125°C, and dried at 75°C for 5 hours to obtain a silicon carbide / phenolic resin composite material; Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.6:1.25:0.15:70:6:7.8; Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene in a mass ratio of 40:23:4.5:3.5:23:7:6.5:18 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0023] Example 4 This embodiment discloses a method for preparing a high-emissivity energy-saving coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS, and toluene in a mass ratio of 8:48:230, ultrasonically dispersing for 25 minutes, reacting for 14 hours at 25°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 7 times the mass of the filter cake to wash three times, and drying at 85°C for 22 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:45, and stirred at room temperature for 4 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and water 6 times the mass of the filter cake was added to wash the mixture until it was neutral, and the mixture was dried at 110°C for 5 hours to obtain pretreated silicon carbide powder. γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed at a mass ratio of 0.11:100:90 and ball-milled for 12 hours, and dried at 110°C for 9 hours to obtain vinyl silicon carbide. The mercapto POSS comprises the following steps to prepare: (3-mercaptopropyl)trimethoxysilane is mixed with methanol, and a 37wt% aqueous solution of hydrogen chloride is added. The volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% aqueous solution of hydrogen chloride is 15.5:380:36.5. The mixture is stirred at 95°C for 33h. After the reaction is completed, the mixture is allowed to stand for cooling for 0.8h. The supernatant is filtered out to remove the precipitate. The precipitate is dissolved by adding 8 times the mass of dichloromethane, and then 10 times the mass of methanol at 0°C is added for precipitation. The dissolution and precipitation operations are repeated once to obtain a crude reaction product. The crude reaction product is mixed and dissolved with dichloromethane at a mass ratio of 1:7, and then 8 times the mass of water is added to extract the crude reaction product. The organic phase is separated, and anhydrous magnesium sulfate of 20wt% of the mass of the organic phase is added to stand for dehydration for 0.8h. The mixture is filtered and the filtrate is evaporated to remove the solvent dichloromethane at 25°C to obtain mercapto POSS. Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 15 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:22 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.58:20:16.5, and the dropping time is 50 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 5 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 25°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene are mixed and reacted at 120°C for 6 hours. After the reaction, phenolic silicon carbide and paraformaldehyde are added and the reaction is continued at 105°C for 3 hours. After the reaction is completed, the solvent toluene is removed by rotary evaporation at 125°C and dried at 75°C for 5 hours to obtain a silicon carbide / phenolic resin composite material; Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.7:1.28:0.15:70:6:7.9; Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene in a mass ratio of 40:24:4.8:3.8:24:6:7:18 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0024] Example 5 This embodiment discloses a method for preparing a high-emissivity energy-saving coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS and toluene in a mass ratio of 8:50:250, ultrasonically dispersing for 30 minutes, reacting for 12 hours at 30°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 8 times the mass of the filter cake to wash three times, and drying at 90°C for 20 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:50, and stirred at room temperature for 5 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and washed with water 8 times the mass of the filter cake until it was neutral, and dried at 120°C for 4 hours to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed at a mass ratio of 0.12:100:100, ball-milled for 12 hours, and dried at 120°C for 8 hours to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: Mix (3-mercaptopropyl)trimethoxysilane with methanol, add 37wt% hydrogen chloride aqueous solution, the volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% hydrogen chloride aqueous solution is 16:400:37, stir and react at 100°C for 30h, after the reaction is completed, let it stand and cool for 1h, filter and remove the supernatant, take the precipitate, add 8 times the mass of dichloromethane to dissolve it, then add 10 times the mass of precipitate methanol at 0°C to precipitate, repeat the dissolution and precipitation operation once to obtain a crude reaction product; mix and dissolve the crude reaction product with dichloromethane in a mass ratio of 1:8, then add 10 times the mass of water to extract the crude reaction product, separate the liquids, take the organic phase, add 20wt% of anhydrous magnesium sulfate by mass of the organic phase, let it stand and remove water for 0.5h, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation at 30°C to obtain mercapto POSS; Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 20 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:20 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.6:22:17, and the dropping time is 60 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 6 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 30°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene were mixed and reacted at 125°C for 5 hours. After the reaction, phenolic silicon carbide and polyformaldehyde were added and the reaction was continued at 110°C for 2.5 hours. After the reaction was completed, the solvent toluene was removed by rotary evaporation at 130°C and dried at 80°C for 4 hours to obtain a silicon carbide / phenolic resin composite material. Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.8:1.3:0.2:80:6:8; Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene in a mass ratio of 40:25:5:4:25:5:8:20 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0025] Comparative Example 1 This comparative example discloses a method for preparing a coating, comprising the following steps: Silicon carbide powder, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent xylene are uniformly mixed in a mass ratio of 40:20:4:3:20:10:5:15 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0026] Comparative Example 2 This comparative example discloses a method for preparing a coating, comprising the following steps: Step (1), mixing alkenyl silicon carbide, mercapto POSS and toluene in a mass ratio of 8:40:200, ultrasonically dispersing for 20 minutes, reacting for 16 hours at 20°C in ultraviolet light with a wavelength of 365nm, filtering after the reaction, taking the filter cake, adding toluene 6 times the mass of the filter cake to wash three times, and drying at 80°C for 24 hours to obtain mercapto silicon carbide; Wherein, alkenyl silicon carbide is prepared by the following steps: The silicon carbide powder was mixed with a 0.1 mol / L aqueous solution of hydrogen chloride at a mass ratio of 1:40, and stirred at room temperature for 3 hours. After the treatment, the mixture was centrifuged and filtered to obtain a filter cake, and washed with water 5 times the mass of the filter cake until it was neutral, and dried at 100°C for 6 hours to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol were mixed and ball-milled at a mass ratio of 0.1:100:80 for 10 hours, and dried at 100°C for 10 hours to obtain vinyl silicon carbide; The mercapto POSS comprises the following steps to prepare: Mix (3-mercaptopropyl)trimethoxysilane with methanol, add 37wt% hydrogen chloride aqueous solution, the volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and 37wt% hydrogen chloride aqueous solution is 14:350:35, stir and react at 90°C for 36h, after the reaction is completed, let it stand and cool for 0.5h, filter and remove the supernatant, take the precipitate, add 5 times the mass of dichloromethane to dissolve the precipitate, then add 8 times the mass of precipitate to precipitate at 0°C, repeat the dissolution and precipitation operation once to obtain a crude reaction product; mix and dissolve the crude reaction product with dichloromethane in a mass ratio of 1:6, then add 8 times the mass of water to extract the crude reaction product, separate the liquids, take the organic phase, add 15wt% of anhydrous magnesium sulfate by mass of the organic phase, let it stand and remove water for 1h, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation at 20°C to obtain mercapto POSS; Step (2), mercapto silicon carbide, dibutylamine and acetone are mixed, ultrasonically dispersed for 10 minutes, and a 4-hydroxyphenyl acrylate-acetone mixed solution prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:25 is added dropwise, the mass ratio of mercapto silicon carbide, dibutylamine, acetone and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.5:18:15, and the dropping time is 40 minutes. After the dropwise addition is completed, the reaction is stirred at room temperature for 4 hours. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 20°C to obtain phenolic silicon carbide; Phenol, boric acid, catalyst oxalic acid and toluene are mixed and reacted at 115°C for 6 hours. After the reaction, phenolic silicon carbide and polyformaldehyde are added and the reaction is continued at 100°C for 3 hours. After the reaction is completed, the solvent toluene is removed by rotary evaporation at 120°C and dried at 70°C for 6 hours to obtain a silicon carbide / phenolic resin composite material. Among them, the mass ratio of phenol, boric acid, catalyst oxalic acid, toluene, phenolic silicon carbide, and paraformaldehyde is 4.4:1.2:0.1:60:6:7.6; Step (3), mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, silicone resin, glass powder, and solvent xylene in a mass ratio of 40:20:4:3:30:5:15 to obtain a high-emissivity energy-saving coating; wherein the preparation of the nickel-doped lanthanum aluminate-based ceramic powder is the same as that in Example 1.
[0027] In the above embodiments and comparative examples: silicon carbide powder comes from Lingke Element Technology Co., Ltd., with an average particle size of 2 μm; γ-(methacryloyloxy)propyltrimethoxysilane comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 2530-85-0; (3-mercaptopropyl)trimethoxysilane comes from Shanghai McLean Biochemical Technology Co., Ltd., CAS No.: 4420-74-0; 4-hydroxyphenyl acrylate comes from Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS No.: 3233-36-1; paraformaldehyde comes from Shanghai Aladdin Biochemical Technology Co., Ltd., with chemically pure specifications, CAS No.: 30525-89-4; polyborosilazane comes from Anhui Aiyota Silicone Oil Co., Ltd., with the product name organic polyborosilazane IOTA-9120; adhesive comes from Anhui Aiyota Silicone Oil Co., Ltd., with the product name borosilazane adhesive IOTA H11500; the silicone resin is from Dow Corning, product name silicone resin 840; glass powder, alumina, silicon dioxide, lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate, and nickel chloride hexahydrate are all commercially available.
[0028] Test example The coatings prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-2 were dispersed uniformly, sprayed on the ceramic fiberboard substrate, and cured at 200° C. for 2 hours to form a coating with a thickness of 30 μm, which was recorded as Sample 1-7. The performance of Sample 1-7 was tested, and the specific test results are shown in Table 1: ; The tests of the various indicators in Table 1 are based on the following standards: adhesion is measured with reference to GB / T1720-1989 "Determination of adhesion of paint films"; impact strength is measured with reference to GB / T 1732-2020 "Determination of impact resistance of paint films"; emissivity is tested by using the IR-2 dual-band emissivity tester of Shanghai Chengbo Optoelectronic Technology Co., Ltd., the test temperature is 600℃, and the band is 1-22μm; the test method for thermal shock resistance includes: keeping samples 1-7 at 1200℃ for 2min, transferring them to ice water at 0℃ for cooling for 2min after the insulation, repeating the insulation and cooling process 20 times, and observing whether the surface morphology of the samples has cracking, shedding and other faults; heat resistance is represented by the heat resistance time, that is, the sample coating does not have cracking, shedding and other faults during the test time, and is measured with reference to GB / T 1735-2009 "Determination of heat resistance of paints and varnishes", and the test temperature is 1600℃.
[0029] It can be seen from the test results in Table 1 that the coating prepared by the present invention has good mechanical properties, good thermal shock resistance and high emissivity after being coated on a substrate and cured.
[0030] The silicon carbide surface in Comparative Example 1 is not modified, lacks the surface modification effect of the boron-containing phenolic resin material and the POSS structure on the silicon carbide, is easily agglomerated, the adhesion of the coating is reduced, and the ceramic structure generated by the ceramicization reaction at high temperature is reduced. In Sample 6 prepared from Comparative Example 1, the heat resistance and thermal shock resistance of the coating are reduced.
[0031] In Comparative Example 2, polyborosilazane and adhesive were replaced with silicone resin. Due to the lack of organic polyborosilazane undergoing ceramic reaction under high-temperature ablation environment to be converted into a ceramic structure with high temperature resistance and high bonding strength, the heat resistance and thermal shock resistance of the coating in Sample 7 prepared in Comparative Example 2 were reduced.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-emissivity energy-saving coating, characterized in that: The following steps are involved: Step (1), mixing alkenyl silicon carbide, mercapto POSS and toluene, ultrasonically dispersing and reacting, and after the reaction is completed, filtering, washing and drying to obtain mercapto silicon carbide; Step (2), mixing mercapto silicon carbide, dibutylamine and acetone, ultrasonically dispersing, dropping 4-hydroxyphenyl acrylate-acetone mixed solution, reacting after the dropwise addition, and rotary evaporating after the reaction to obtain phenolic silicon carbide; Phenol, boric acid, a catalyst and toluene are mixed and reacted. After the reaction is completed, phenolic silicon carbide and paraformaldehyde are added and the reaction is continued. After the reaction is completed, the silicon carbide / phenolic resin composite material is obtained by rotary evaporation and drying. Step (3), uniformly mixing the silicon carbide / phenolic resin composite material, nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent to obtain a high-emissivity energy-saving coating.
2. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: In the step (1), the mass ratio of alkenyl silicon carbide, mercapto POSS and toluene is 8:40-50:200-250; the reaction conditions are: reacting for 12-16 hours at a temperature of 20-30° C. under ultraviolet light with a wavelength of 365 nm.
3. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: The alkenyl silicon carbide in step (1) is prepared by the following steps: The silicon carbide powder is mixed with a hydrogen chloride aqueous solution, stirred, and after the treatment, centrifuged, filtered, washed, and dried to obtain pretreated silicon carbide powder; γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol are mixed and ball-milled, and dried to obtain vinyl silicon carbide.
4. The method for preparing a high-emissivity energy-saving coating according to claim 3, characterized in that: When preparing alkenyl silicon carbide: the mass ratio of silicon carbide powder to hydrogen chloride aqueous solution is 1:40-50, and the hydrogen chloride aqueous solution is 0.1 mol / L hydrogen chloride aqueous solution; the stirring treatment conditions are: stirring treatment at room temperature for 3-5 hours; the mass ratio of γ-(methacryloyloxy)propyltrimethoxysilane, pretreated silicon carbide powder, and ethanol is 0.1-0.12:100:80-100; and the ball milling time is 10-12 hours.
5. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: The mercapto POSS in step (1) is prepared by the following steps: (3-Mercaptopropyl)trimethoxysilane is mixed with methanol, and a hydrogen chloride aqueous solution is added, and the mixture is stirred for reaction. After the reaction is completed, the mixture is allowed to stand for cooling, filtered, and purified to obtain mercapto POSS.
6. The method for preparing a high-emissivity energy-saving coating according to claim 5, characterized in that: When preparing the mercapto POSS: the volume ratio of (3-mercaptopropyl)trimethoxysilane, methanol and hydrogen chloride aqueous solution is 14-16:350-400:35-37, and the hydrogen chloride aqueous solution is 37wt% hydrogen chloride aqueous solution; the stirring reaction conditions are: stirring the reaction at 90-100°C for 30-36h.
7. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: In the step (2), the mass ratio of mercapto silicon carbide, dibutylamine, acetone, and 4-hydroxyphenyl acrylate-acetone mixed solution is 5:0.5-0.6:18-22:15-17; the 4-hydroxyphenyl acrylate-acetone mixed solution is prepared by mixing 4-hydroxyphenyl acrylate and acetone in a mass ratio of 1:20-25, and the dropwise addition time is 40-60 minutes; when preparing phenolic silicon carbide, the reaction conditions are: stirring the reaction at room temperature for 4-6 hours.
8. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: In the step (2), the mass ratio of phenol, boric acid, catalyst, toluene, phenolic silicon carbide and polyformaldehyde is 4.4-4.8:1.2-1.3:0.1-0.2:60-80:6:7.6-8. When preparing the silicon carbide / phenolic resin composite material, the reaction conditions are: reacting at a temperature of 115-125°C for 5-6h, and the continued reaction conditions are: continuing the reaction at a temperature of 100-110°C for 2.5-3h.
9. The method for preparing a high-emissivity energy-saving coating according to claim 1, characterized in that: In the step (3), the mass ratio of the silicon carbide / phenolic resin composite material, the nickel-doped lanthanum aluminate-based ceramic powder, alumina, silicon dioxide, polyborosilazane, adhesive, glass powder, and solvent is 40:20-25:4-5:3-4:20-25:5-10:5-8:15-20.
10. A high-emissivity energy-saving coating prepared by the method for preparing a high-emissivity energy-saving coating as described in any one of claims 1 to 9.
Citation Information
Patent Citations
High-temperature-resistant and high-radiation-resistant thermal control coating and preparation method thereof
CN105111935A
Cited By
La-doped Cu-Cr-Ti series high-emissivity ceramic coating as well as preparation method and application thereof
CN121427348A